A Literature Review: Relationship between Interleukin-1 Beta and the Severity of COVID-19 - Andi Ita Maghfirah; Tenri Esa; Uleng Bahrun (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
COVID-19 disease can cause dysregulation of the immune system, resulting in a cytokine storm. One of the cytokines released is IL-1B, a proinflammatory cytokine due to macrophage stimulation. This study aimed to provide a literature review of the value of Interleukin-1 beta (IL-1B) in patients with severity of COVID-19. This literature review was carried out using the search engines PubMed, Open Accessed Journal, Science Direct, and Google Scholar from December 2019 to December 2022. No studies suggested that IL-1B was associated with the severity of COVID-19. IL-1B is vital during the acute inflammatory response and helps T cells by linking innate and adaptive immunity as a lymphocyte activation factor. A gradual decrease in lymphocyte count was reported in severe COVID-19 diseases. The substantial reduction in lymphocyte count indicates that the SARS-CoV-2 virus increases immune cells and inhibits cellular immunity. This result might explain why IL-1B levels in mild COVID-19 were not significantly different from IL-1B levels in severe COVID-19. There was an increase in IL-1B levels in COVID-19 patients, but there was no relationship between IL-1B and the severity of COVID-19.